Optimized reduced representation bisulfite sequencing reveals tissue-specific mCHH islands in maize - Hsu, Fei-Man (Epigenetics Chromatin, 2017)
BACKGROUND: DNA methylation plays important roles in many regulatory processes in plants. It is economically infeasible to profile genome-wide DNA methylation at a single-base resolution in maize, given its genome size of ~2.5 Gb. As an alternative, we adapted region of interest (ROI)-directed reduced representation bisulfite sequencing (RRBS) to survey genome-wide methylation in maize. RESULTS: We developed a pipeline for selecting restriction enzymes in silico and experimentally showed that, in the maize genome, MseI- and CviQI-digested fragments are precisely enriched in promoters and gene bodies, respectively. We proceeded with comparisons of epigenomes and transcriptomes between shoots and tassels and found that the occurrences of highly methylated, tissue-specific, mCHH islands upstream of transcription start sites (TSSs) were positively correlated with differential gene expression. Furthermore, 5′ regulatory regions between TSS and mCHH islands often contain putative binding sites of known transcription factors (TFs) that regulate the flowering process and the timing of the transition from the vegetative to the reproductive phase. By integrating MNase-seq and siRNA-seq data, we found that regions of mCHH islands accumulate 21nt-siRNAs in a tissue-specific manner, marking the transition to open chromatin, thereby ensuring the accessibility of TFs for tissue-specific gene regulation. CONCLUSIONS: Our ROI-directed RRBS pipeline is eminently applicable to DNA methylation profiling of large genomes. Our results provide novel insights into the tissue-specific epigenomic landscapes in maize, demonstrating that DNA methylation and siRNA and chromatin accessibility constitute a critical, interdependent component that orchestrates the transition from the vegetative to the reproductive phase. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13072-017-0148-y) contains supplementary material, which is available to authorized users.